Two patients with chronic mucocutaneous candidiasis caused by TRAF3IP2 deficiency - ÖZEN, AHMET OĞUZHAN; AYDINER, ELİF; BARIŞ, SAFA (MOSBY-ELSEVIER, 2021)
Background: TRAF3 interacting protein 2 (TRAF3IP2) (Act1) is an adapter protein that interacts with IL-17R via its similar expression to fibroblast growth factor genes and IL-17R domain and coordinates 2 separate proinflammatory pathways following IL-17 cytokine stimulation. Objective: We sought to elucidate the immunologic consequences of TRAF3IP2 homozygous mutations to improve treatments for immunodeficiency patients with chronic mucocutaneous candidiasis. Methods: We describe 2 patients presenting with chronic mucocutaneous candidiasis who harbor biallelic nonsense mutations in TRAF3IP2. The cellular and molecular features of this genetic defect were assessed using in vitro cytokine assays and protein analysis. Results: We show that the homozygous mutation causes complete loss of protein expression. We also show that the absence of TRAF3IP2 was associated with a defective response to combined IL-2/IL-25 (IL-17E) stimulation. Conclusions: Failure to initiate normal signaling downstream of IL-17R engagement likely contributes to the patients' recurrent fungal infections. These findings add to our molecular understanding of genetic defects affecting this critical pathway of antifungal immunity. (J Allergy Clin Immunol 2021;148:256-61.)
Keywords: TRAF3IP2; Act1; IL-17; signaling; chronic mucocuta-neous candidiasis; antifungal immunity; recurrent fungal infections; MUTATION; DISEASE; ACT1